IMPLEMENTATION OF VILLAGE OWNED ENTERPRISE PROGRAM POLICY IN LAMU VILLAGE, TILAMUTA DISTRICT, BOALEMO DISTRICT - Poliyama, Magfirah; Tui, Fenti Prihatini; Tantu, Romy (Public Policy Journal, 2024)
This study aims to determine and analyze the Policy Implementation of the Village-Owned Enterprise Program in Lamu Village, Tilamuta District, Boalemo Regency, in terms of Communication, Resources, Disposition and Bureaucratic Structure. This research method uses a qualitative approach with a type of Qualitative Descriptive research, while the data collection techniques used are observation and documentation. Based on the results of research analyzed in the field that (1) the Policy Implementation Process of Village-Owned Enterprises Program in Lamu, Tilamuta District, Boalemo Regency includes aspects Communication carried out  by managers  with the community, it  is sufficient to be applied by BUMDes managers because the information  obtained is clear in terms of information, transparency of the BUMDes ProgramHowever, there are still people who do not know the programs implemented because the community does not attend meetings held by the Village Government and BUMDes Management. Resources, which exist  in the management of BUMDes are quite good, in this case Human resources can beseen from the managers of BUMDes have  greatly supported the success of existing BUMDes activities  , but in terms of facilities that support BUMDes program policies have not been fulfilled properly.    Disposition, the executors of Village-Owned Enterprises behave in accordance with the existing rules  in  BUMDes, but have not been optimal and professional in carrying out their duties and functions because managers still need to learn and need guidance, in addition to the attitude of the management that is not open, and  the Bureaucratic Structure, regarding the BUMDes Program do well based on AD / ART regulations and SOPs so that the programs carried out are not neglected / failed.